An Analysis of Leadership Styles in Shaping Religious Character in Islamic Boarding Schools Amal Jama'i Bojong Cikembar Sukabumi - Abdul Halim Muhammad; Wipkil Basor; Jajat Sudrajat; Farras Abdillah; Ubaidah Ubaidah (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to analyze leadership styles in shaping the religious character of students at the Amal Jama'i Cikembar Sukabumi Islamic Boarding School. The background of this study is based on the phenomenon of moral crisis among students and the importance of strengthening character education based on religious values. The study used a qualitative method with a narrative-descriptive approach. Data were obtained through observation, interviews with leaders, asatidzah, and dormitory supervisors, as well as documentation studies, then analyzed using the Miles and Huberman model. The results show that the leadership style in the Islamic boarding school is integrative, combining transformational, situational, and prophetic approaches by emphasizing a balance between assertiveness and a humanist approach. The implementation of leadership is carried out through exemplary behavior, habituation, educational discipline, and continuous supervision in a 24-hour guidance system. This leadership style has proven effective in shaping the religious character of students holistically, as indicated by increased discipline in worship, strengthening morals, growing spiritual awareness, and harmonious social relationships. The main supporting factors include the religious environment of the Islamic boarding school, a structured guidance system, and synergy between institutional elements. Inhibiting factors include the heterogeneity of student backgrounds, unequal discipline, external influences, and limited facilities and human resources. Therefore, values-based integrative leadership significantly contributes to shaping the religious character of students and has the potential to become a model for developing Islamic educational leadership in facing the challenges of the times.